Tapatybės virsmo istorija: Vaižganto Pragiedruliai ir 1918–1920 m. konfliktas dėl Vilniaus - Kvietkauskas, Mindaugas (Literatūra, 2015)
This article deals with the problem of representation of the Lithuanian national identity in the novel Pragiedruliai (Bright Spaces) by Juozas Tumas-Vaižgantas (1869–1933). The classical novel, which was planned to become an epos of the Lithuanian national revival, was published in three parts during 1918–1920 in Vilnius, at the height of political and military conflict between Lithuania and Poland over the possession of this multinational city. The author himself was one of the main Lithuanian combatants in the field of nationalist ideology and press as he edited the main Lithuanian dailies (Lietuvos Aidas, Nepriklausomoji Lietuva) in Vilnius in that period. In his numerous press articles, Vaižgantas discussed Lithuanian identity as a phenomenon born from the local spirit of nature, formed by the primeval forces of biosphere, and organically evolving into the modern state of national consciousness. By suggesting this model of “organically modern” and “naturally democratic” Lithuanian identity, Vaižgantas was creating an antithesis against the image of Lithuanians as uncivilized barbarians propagated by the Polish nationalist side. However, the novel Pragiedruliai reveals much more diverse and complicated process of conversion of the “natural” or “pantheist” Lithuanian consciousness into the modern national selfimage. While trying to elaborate the symbolic literary narrative of this identity transformation, Vaižgantas included intertextual references to Pan Tadeusz, a 19th century Polish epos about the Lithuanian Grand Duchy noblemen by Adam Mickiewicz, as well as symbols indicating the intricate link between the Lithuanian identity and the cultural history of the Grand Duchy. The original opening chapters of Vaduvų kraštas (The Land of Vaduvos), the second volume of the novel, presented an acute criticism of the Lithuanian “natural” consciousness from the perspective modern cultural liberalism. Thus the clear construction of identity used by Vaižgantas in his political rhetoric becomes complicated and in some cases is even undermined in the polysemantic literary texture of his novel.